Efforts to Improve Mathematics Learning Outcomes in Class III Materials for Measurement of Time Units at SDN Pende 03 Using Analog Clock - Rizki Rahmawati (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This research was carried out with the aim of improving the mathematics learning outcomes of third grade students at SDN Pende 03 by using analog clock teaching aids on time unit measurement material. This type of research is classroom action research (CAR). The subjects were class III students, totaling 23 students. This CAR design includes planning, implementation, observation (evaluation), and reflection. Data collection techniques using observation, tests, and documentation. Data analysis used quantitative descriptive statistics. The results showed an increase in the percentage of student learning outcomes, this can be seen from each cycle. It was found that student learning outcomes increased compared to the pre-cycle average score of 51.96 to 63.48 in the first cycle, then to 72.17 in the second cycle. Thus, it can be concluded that the use of analog clock teaching aids in time unit measurement material can improve student learning outcomes.